Effect of the precipitation state on high temperature tensile and creep behaviors of Mg-15Gd alloy - Shuxia Ouyang; Guangyu Yang; He Qin; Chunhui Wang; Shifeng Luo; Wanqi Jie (Journal of Magnesium and Alloys, 2022)
Due to the effective precipitation strengthening effect of the β′ phase, Mg-Gd alloys exhibit excellent room temperature mechanical behaviors. However, when served at high temperatures, the metastable β′ phase will transform to other phases, resulting in severe performance degradation. In this study, we investigated the effect of precipitation state achieved by different heat treatments on high temperature tensile and creep behaviors of the Mg-15Gd alloy by comparing the properties of the as-cast, solid-solutioned (T4) and peak-aged (T6) alloys. The results showed that the tensile mechanical properties of the T6 alloy were always highest from room temperature to 300 °C, in spite of an abnormal strength increase with temperature existed in the T4 alloy. For tensile creep properties, the T6 alloy exhibited the lowest steady creep rate below 235 °C while the T4 alloy possessed the best properties above 260 °C. Microstructure characterization revealed that the transition was caused by the stress-promoted precipitation of β′ phase in the T4 alloy and rapid phase transformation in the T6 alloy at high temperatures. At 260 °C, the calculated stress exponent n was 3.1 and 2.8 for the T4 and T6 alloys, respectively, suggesting the creep deformation mechanism was dislocation slip, which was further confirmed by the microstructure after creeping. Our findings can provide new insights into the heat treatment process of Mg-Gd alloys served at high temperatures.